2023
DOI: 10.1108/cdi-10-2022-0274
|View full text |Cite
|
Sign up to set email alerts
|

Evolving as an entrepreneur: a life story approach to studying Indian women entrepreneurs

Abstract: PurposeThe purpose of this article is to understand how women develop entrepreneurship as a career identity through women's various life stages. Using a life story approach, the authors study the formation of Indian businesswomen's entrepreneurial identity in businesswomen's unique socio-cultural context.Design/methodology/approachThe study drew upon 15 semi-structured interviews with practicing women entrepreneurs using a qualitative methodology. Gioia methodology was used to systematically analyze the data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
(120 reference statements)
0
0
0
Order By: Relevance
“…This aligns with the view that the interplay between work and nonwork is bounded due to finite time and resources (Demerouti and Bakker, 2023). Moreover, national governments may wish to consider the pros and cons of introducing Universal Basic Income (Perkins et al, 2022) or other support measures, given the value of entrepreneurial pursuits to the economy in India (Khattar and Agarwal, 2023).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…This aligns with the view that the interplay between work and nonwork is bounded due to finite time and resources (Demerouti and Bakker, 2023). Moreover, national governments may wish to consider the pros and cons of introducing Universal Basic Income (Perkins et al, 2022) or other support measures, given the value of entrepreneurial pursuits to the economy in India (Khattar and Agarwal, 2023).…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, national governments may wish to consider the pros and cons of introducing Universal Basic Income (Perkins et al. , 2022) or other support measures, given the value of entrepreneurial pursuits to the economy in India (Khattar and Agarwal, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Au et al (2021) found that government support in Malaysia increased the likelihood of women entering and staying in an entrepreneurship path. Khattar and Agarwal (2023) also found that for women in India, "entrepreneurial identity was a developmental process influenced by various episodes in different life stages-childhood, adolescence, marriage and motherhood" (p. 277). This perhaps also explains some of the conflicting findings in the literature around the role of gender as a moderator between different variables across various Encouraging students to become entrepreneurs countries and regions.…”
Section: Encouragingmentioning
confidence: 99%